The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1099/0022-1317-71-1-219
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of the 58K and 48K Proteins in the Intercellular Movement of Cowpea Mosaic Virus

Abstract: Infection of cowpea cells with cowpea mosaic virus (CPMV) is accompanied by the appearance of tubular structures containing virus-like particles which protrude from or penetrate the cell wall. Immunogold labelling of sections of infected cells using antisera against a CPMV M RNA translation products, and Protein A -g o l d , showed that the 58K and/or 48K tentative transport proteins of CPMV were located in or on these tubular structures. Furthermore, these proteins were detected in small electron-dense areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 21 publications
(19 reference statements)
3
77
0
Order By: Relevance
“…Furthermore, immunofluorescence studies on the location of the 58K/48K movement proteins show that these proteins are also present over the whole length of the tubule. These results agree with our present and earlier observations from immunogold labelling of ultrathin sections of protoplasts and plant tissues (van Lent et al, 1990b). The exact location of the movement proteins could not be determined by labelling of negatively stained preparations because tubules were only labelled with antibodies against the 58K/48K proteins when the structure of the tubule had apparently disintegrated or was absent.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, immunofluorescence studies on the location of the 58K/48K movement proteins show that these proteins are also present over the whole length of the tubule. These results agree with our present and earlier observations from immunogold labelling of ultrathin sections of protoplasts and plant tissues (van Lent et al, 1990b). The exact location of the movement proteins could not be determined by labelling of negatively stained preparations because tubules were only labelled with antibodies against the 58K/48K proteins when the structure of the tubule had apparently disintegrated or was absent.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, we have shown that the 58K/48K movement proteins of CPMV are localized to the tubular structures extending from plasmodesmata of infected cells, suggesting that these structures are involved in cell-to-cell movement (van Lent et al, 1990b). The limited ultrastructure detectable in ultrathin sections of tissue embedded at low temperature and the poor resolution of immunogold labelling make it difficult to determine the exact location of proteins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunogold labelling has shown that the CPMV MP is present in these tubular structures (van Lent et al, 1990). On the surface of CPMV-infected protoplasts, similar tubular structures are formed, which protrude up to 20 mm into the culture medium, are tightly surrounded by the plasma membrane and have the same ultrastructure as tubules in plant tissue (van Lent et al, 1991).…”
Section: Introductionmentioning
confidence: 86%